Prototype of a heart monitor implementing IOT: Desarrollo de un Prototipo de monitor cardiaco implementando IOT (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
The objective of the study is to develop an ambulatory cardiac monitoring prototype implementing IoT. The present work shows the development of a device capable of studying heart rate using IoT technology.The device developed has features such as amplifying, filtering and conditioning the cardiac signal thanks to its architecture and the three electrodes connected to specific points on the human body. When acquiring this data, it is sent through a programmable development module which connects to the Internet via WiFi and sends the information obtained to a web server in the cloud.